The Effects of Immersion and Visuo-Tactile Stimulation on Motor Imagery in Stroke Patients are Related to the Sense of Ownership - Zhe Song; Xiting Zhang; Xiaotian Xu; Jiaoyang Dong; Wei Li; Yih-Kuen Jan; Fang Pu (IEEE, 2024)
Visual guided motor imagery (MI) is commonly used in stroke rehabilitation, eliciting event-related desynchronization (ERD) in EEG. Previous studies found that immersion level and visuo-tactile stimulation could modulate ERD during visual guided MI, and both of two factors could also improve sense of ownership (SOO) over target limb (or body). Additionally, the relationship was also reported between the performance of MI and SOO. This study aims to investigate whether immersion and visuo-tactile stimulation affect visual guided MI through the SOO over virtual body in stroke patients. Nineteen stroke patients were recruited. The experiment included two phases (i.e., SOO induction and visual guided MI with SOO) that was manipulated across four conditions in a within-subject design: ${2}× {2}$ , i.e., immersion (VR, 2D monitor display) $× $ multisensory stimulation (visuo-tactile stimulation, observation without tactile stimulation). Results found peaks ERD amplitude during MI were significantly higher in stronger SOO conditions than weaker SOO conditions. Interestingly, the ERD during visual guided MI under the condition of vision only in VR and visuo-tactile stimulation in 2D monitor are similar, which indicates that SOO may be an important factor behind this phenomenon (due to the similar SOO between these two conditions). A moderate correlation was also found between SOO scores and peaks ERD amplitude during MI. This study discussed the possible factor underlying the effects of immersion and multisensory stimulation on visual guided MI in post-stroke patients, identifying the effect of SOO in this process, and could be referred in future studies for coming up with better MI paradigms for stroke rehabilitation.